The Influence Of Strategic Management Accounting And Information Technology Capability On Company Performance With Sustainable Competitive Advantage As The Mediator - Indrawati Marpaung, Elyzabet; Aryati, Titik; Augustine, Yvonne (International Journal of Educational Research & Social Sciences, 2022)
This study analyzes the influence of strategic management accounting and information technology capability on company performance and examines sustainable competitive advantage that can mediate the effect of strategic management accounting and information technology capability on company performance. The population of this study was companies from raw materials, industry, primary and non-primary consumer goods, and health sectors in Indonesia. Meanwhile, the research respondents were the employees of these companies. To collect the respondents’ responses, we employed the survey method. The employees’ responses from the same company were averagely calculated to be one value; therefore, one value stands for one company. This study employed 203 relevant companies so that it employed a structural equation model based on covariance. The hypothesis examination has revealed that strategic management accounting has a positive effect on sustainable competitive advantage. Sustainable competitive advantage has a positive effect on company performance. In contrast, strategic management accounting and information technology capability do not affect company performance. Information technology capability has no effect on sustainable competitive advantage. Sustainable competitive advantage can mediate the influence of strategic management accounting on company performance. Sustainable competitive advantage cannot mediate the effect of information technology capability on company performance.Finally, the application of strategic management accounting enables companies to achieve sustainable competitive advantage and ultimately improve company performance.